2022
DOI: 10.1038/s12276-022-00781-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthase 2, a target of miR-200c, promotes carbon tetrachloride-induced acute and chronic liver inflammation via regulation of CCL3 and CCL4

Abstract: Liver fibrosis occurs during wound healing after repeated liver injury and is characterized by extensive extracellular matrix deposition. We previously identified hyaluronan synthase 2 (HAS2) as a driver of liver fibrosis and hepatic stellate cell (HSC) activation. Developing strategies to suppress HSC activation is key to alleviating liver fibrosis, and HAS2 is an attractive candidate for intervention. To gain insight into the molecular function of HAS2, we investigated its posttranscriptional regulation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Activated hepatic stellate cells (HSC) express hyaluronan synthase (HAS2) 38 , which is involved in the accumulation of HA in the liver. HAS2 and HA further promote HSC activation and fibrosis 38 , 39 and are detected in the blood of animals with advanced liver fibrosis 38 . In this study, HA levels were elevated in some individuals in the TAA group.…”
Section: Discussionmentioning
confidence: 99%
“…Activated hepatic stellate cells (HSC) express hyaluronan synthase (HAS2) 38 , which is involved in the accumulation of HA in the liver. HAS2 and HA further promote HSC activation and fibrosis 38 , 39 and are detected in the blood of animals with advanced liver fibrosis 38 . In this study, HA levels were elevated in some individuals in the TAA group.…”
Section: Discussionmentioning
confidence: 99%
“…CCL4 belongs to the macrophage inflammatory protein-1 (MIP-1) family, which recruits immune cells and is produced by hepatic stellate cells, macrophages and monocytes, in the liver ( 35 ). Krohn et al.…”
Section: Discussionmentioning
confidence: 99%
“…CCL4 belongs to the macrophage inflammatory protein-1 (MIP-1) family, which recruits immune cells and is produced by hepatic stellate cells, macrophages and monocytes, in the liver (35). Krohn et al found that CCL4 plays an important role in the early induction of immune cell infiltration after hepatocyte transplantation (36).…”
Section: Discussionmentioning
confidence: 99%
“…miR-200c is downregulated by liver fibrosis, binds to the 3’-UTR of HAS2, and post-transcriptionally regulates HAS2 expression in HSCs (Figure 5 ). 67 Hedgehog (Hh) signaling is another important pathway in HSC activation and liver fibrosis. In Hh signaling, the interaction of sonic Hedgehog ligand and the cell surface receptor Patched releases and activates Smoothened, leading to nuclear localization of glioblastoma family transcription factors (Glis) that regulate the expression of cell-specific target genes.…”
Section: Introductionmentioning
confidence: 99%